Public Speaking Training In An English Community Pilot Program In Metro City, Lampung - Suprihatin, Yeni; Dartiara, Rika; Ninsiana, Widhya (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Everyone who is capable and able to communicate, however, is not necessarily skilled at speaking in public. This limitation occasionally leads to communication misunderstandings. The IAIN Metro Community Service Team studied the English Training and Gathering (Estage) Language Education Institute, which implements the English system in a Metro City - Lampung area as a forum for improving the speaking skills and quality of members from elementary to advanced classes, supported by gathering activities that encourage students to dare to speak in public. The service training activities were given to helpg students at the English Village Estage understanding the elements and processes of public speaking. Participant skills in public speaking, such as the ability to think on the go, develop vocals to have a microphonic voice, and get used to speaking without primarily relying on text, some participants were found need ongoing preparation and adaptation to public speaking. The main ways of becoming prepared for public speaking were to help the participants develop courage and self-confidence, as well as to increase their knowledge and comprehension by continually practicing.            Keywords: english; estage; community service; public speaking